KALKULUS DALAM PENDIDIKAN MATEMATIKA: KAJIAN LITERATUR TENTANG PERAN DAN MANFAATNYA BAGI MAHASISWA - Roby Anta Rikfataka; Nur Aliza Septi Utami; Tina Fitriani; Epa Triana; Cinta Aprilia; Elista Agustin; Meisha Fradisti; M Win Afgani (PHI: Jurnal Pendidikan Matematika, 2026)
This study aims to examine the role and benefits of calculus in mathematics education for university students through a literature review approach. The method used is qualitative research with a literature study of relevant scientific articles published between 2020 and 2025. The results show that calculus plays an important role as a foundation for understanding advanced mathematical concepts and in developing students’ critical, analytical, and problem-solving skills. However, calculus learning still faces several challenges, such as difficulties in understanding abstract concepts, weak basic mathematical skills, and the dominance of procedural approaches. In addition, psychological factors such as motivation and self-efficacy, as well as differences in learning styles, also influence student learning success. Therefore, innovative learning strategies, the use of instructional media, and the integration of digital technology are needed. Thus, effective calculus learning is expected to improve students’ understanding and prepare them to become competent individuals in academic and professional fields.